Pharmacophore-Based Virtual Screening of Novel Inhibitors and Docking Analysis for CYP51A from Penicillium italicum - Yongze Yuan; Rui Han; Qianwen Cao; Jinhui Yu; Jiali Mao; Tingfu Zhang; Shengqiang Wang; Yuhui Niu; Deli Liu (Marine Drugs, 2017)
Sterol 14α-demethylases from Cytochrome P450 family (CYP51s) are essential enzymes in sterol biosynthesis and well-known as the target of antifungal drugs. The 3D structure of CYP51A from Penicillium italicum (PiCYP51A) was constructed through homology modeling based on the crystal structure of human CYP51A (PDB: 3LD6). Molecular dynamics (MD) simulation was operated to relax the initial model and followed by quality assessment using PROCHECK program. On the basis of the docking information on the currently available CYP51s with the patent demethylase inhibitors (DMIs), pharmacophore-based virtual screening combined with docking analysis was performed to pick out twelve new compounds from ZINC database. Six hits revealed in the ligand database suggested potential ability to inhibit PiCYP51A. Compared to patent fungicide triazolone, the top three lead compounds had similar or higher affinity with the target enzyme, and accordingly, exhibited comparable or lower EC50 values to P. italicum isolates. The results could provide references for de novo antifungal drug design.